Equilibrium, kinetic and thermodynamic studies on the adsorption of phenol onto chitin - Dursun, AY; Kalayci, ÇS (Elsevier, 2005)
The adsorption of phenol onto chitin, a naturally occurring material was studied as a function of initial pH, temperature and initial phenol concentration. The highest phenol adsorption capacity was determined as 21.5 mg g(-1) for 300 mg dm(-3) initial phenol concentration at pH 1.0 and 40 degrees C. Adsorption data were well described by the Freundlich Model, although they could be modeled by the Langmuir equation. The pseudo-first-order and pseudo-second-order kinetic models were applied to test the experimental data. The pseudo-second-order kinetic model provided the best correlation of the experimental data compared to the pseudo-first-order model. The thermodynamic constants of the adsorption process; Delta G degrees, Delta H degrees and Delta S degrees were evaluated as -19.4 KJ mol(-1) (at 40 degrees C, 10.2 KJ mol(-1) and 0.093 KJ mol(-1) K-1, respectively. These showed that adsorption of phenol on chitin was endothermic and spontaneous. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; adsorption; chitin; equilibrium; kinetic; thermodynamics